2009
DOI: 10.1128/jb.00370-09
|View full text |Cite
|
Sign up to set email alerts
|

CsrRS Regulates Group BStreptococcusVirulence Gene Expression in Response to Environmental pH: a New Perspective on Vaccine Development

Abstract: To identify factors involved in the response of group B streptococci (GBS) to environmental pH, we performed a comparative global gene expression analysis of GBS at acidic and neutral pHs. We found that the transcription of 317 genes was increased at pH 5.5 relative to that at pH 7.0, while 61 genes were downregulated. The global response to acid stress included the differential expression of genes involved in transport, metabolism, stress response, and virulence. Known vaccine candidates, such as BibA and pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 64 publications
6
100
1
2
Order By: Relevance
“…3E and F). An earlier study found that exposure of strain 2603 to pH 5.5 resulted in a 2-to 3-fold increase in ape1 expression as assessed in transcriptional profiling experiments using genomic microarrays (30). Increased expression of Ape1 could account for the observed upregulation of the PI-1 genes sag0645 and sag0647 at pH 5.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3E and F). An earlier study found that exposure of strain 2603 to pH 5.5 resulted in a 2-to 3-fold increase in ape1 expression as assessed in transcriptional profiling experiments using genomic microarrays (30). Increased expression of Ape1 could account for the observed upregulation of the PI-1 genes sag0645 and sag0647 at pH 5.0.…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise specified, GBS was grown in Todd-Hewitt broth (THB; Difco) or on Trypticase soy agar (TSA) supplemented with 5% defibrinated sheep blood (PML Microbiologicals). For experiments testing the effects of pH, GBS was cultured at 37°C in complex medium (CM; 10 g/liter proteose peptone, 5 g/liter Trypticase peptone, 5 g/liter yeast extract, 2.5 g/liter KCl, 1 mM urea, 1 mM arginine) (30). E. coli was grown in Luria-Bertani broth, and L. lactis was grown in GM17 broth (M17 broth [Oxoid] supplemented with 0.5% glucose) (1).…”
Section: Methodsmentioning
confidence: 99%
“…Dalton & Scott (2004) have reported that the growth of a CovS knockout mutant strain derived from M6 serotype strain JRS4 is impaired at low pH. In addition, Santi et al (2009) have reported that a CovRS homologue in Streptococcus agalactiae is involved in the pH-dependent regulation of gene expression. In this study, we did not identify a significant role for CovS but showed that Spy1622 could be involved in the response to acid stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A GBS mutant of the CovSR ortholog, also known as CsrS/CsrR, displayed impaired viability in human serum and attenuated virulence in murine infection models (506,507). It has been hypothesized that the translocation of GBS from the acidic milieu of the vagina to neonatal tissues with a neutral pH signals the conversion from a colonizing to an invasive phenotype in a CsrRS-dependent manner (508). The CiaHR TCS of S. pneumoniae regulates many genes involved in competence development and virulence, including htrA (see above) (486).…”
Section: Global Transcriptional Regulators and Virulencementioning
confidence: 99%